Cover Feature: In Vivo Energy Transfer from Bacteriochlorophyll c, d, e, or f to Bacteriochlorophyll a in Wild‐Type and Mutant Cells of the Green Sulfur Bacterium Chlorobaculum limnaeum (ChemPhotoChem 3/2018). Issue 3 (13th March 2018) - Harada, Jiro; Shibata, Yutaka; Teramura, Misato; Mizoguchi, Tadashi; Kinoshita, Yusuke; Yamamoto, Ken; Tamiaki, Hitoshi
Abstract : The Cover Feature highlights the importance of chlorosomes, the most efficient light‐harvesting antenna system among phototrophs. Bacteriochlorophylls c, d, e and f self‐aggregate in a chlorosome to transfer excitation energy to bacteriochlorophyll a by means of a Förster mechanism. More information can be found in the Article by J. Harada et al. onpage 190 in Issue 3, 2018 (DOI:10.1002/cptc.201700164 ).